2016
DOI: 10.1016/j.jgeb.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of lovastatin production from Aspergillus fumigatus

Abstract: The present investigation, focused on screening of various fungal species for Lovastatin production using different agro-based wastes, also, for maximizing lovastatin productivity by isolated Aspergillus fumigatus using response surface methodology (RSM). The following substrates (Olive cake; Pea pods; sugarcane bagasse; wheat bran; rice hulls; beet peel; Potato peel and groundnut shells) were screened to evaluate their effectiveness for lovastatin production, using different fungal species, (Aspergillus niger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Consequently, it can be concluded that temperature exerted a significant effect on lovastatin production. This may be due to the fact that increasing the temperature leads to poor heat dissipation and a reduction in the oxygen level, thereby inhibiting the growth of microorganisms (Mouafi et al 2016), which is in agreement with Negishi et al (1986) and Munir et al (2018), who found that increasing the temperature to 35°C inhibited lovastatin production because the metabolic processes of denaturing enzymes and other proteins were retarded.…”
Section: Cultivation Systemsupporting
confidence: 83%
See 1 more Smart Citation
“…Consequently, it can be concluded that temperature exerted a significant effect on lovastatin production. This may be due to the fact that increasing the temperature leads to poor heat dissipation and a reduction in the oxygen level, thereby inhibiting the growth of microorganisms (Mouafi et al 2016), which is in agreement with Negishi et al (1986) and Munir et al (2018), who found that increasing the temperature to 35°C inhibited lovastatin production because the metabolic processes of denaturing enzymes and other proteins were retarded.…”
Section: Cultivation Systemsupporting
confidence: 83%
“…The fungi used in the study, with their yields, were as follows: A. terreus (55 mg/L), A. parasiticus (4.5 mg/L), A. fischeri (2.0 mg/L), A. flavus (9.0 mg/L), A. umbrosus (14.1 mg/L), Penicillium funiculosom (pinophilum)(19.3 mg/L), Trichoderma viridae (9.0 mg/L), Trichoderma longibrachiatum (1.0 mg/L), Acremonium chrysogenum (2.5 mg/L). Mouafi et al (2016) reported that the optimal lovastatin production (3.353 mg/g of dried fermented matter) from A. fumigatus was achieved at a temperature of ~28°C and a pH5.0 with an incubation period of 12 days. Elsewhere, the optimal yield of lovastatin from Monascus ruber, incubated at 25°C, at pH5.0 under submerged fermentation with shaking at 150 rpm for 10 days, was 131 mg/L (Sripalakit et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Spores were counted with a hemocytometer and adjusted to 1 × 10 7 spores/mL. Finally, 2 mL of each suspension was utilized as the inoculum [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bizukojc et al, (2012) reported that neutral and basic pH range produced greater lovastatin formation as acidic ones This is due to effect for polyketide pathways (A. terreus) and the substantial reduce of (+) geodin (Bizukojc and Ledakowicz, 2008). pH also influences lovastatin production (Bizukojc et al, 2012) as pH powerfully effects the transportation of many ingredients through the physiological membrane (Mouafi et al, 2016). Inoculum size in SSF has been studied positive and negative influences.…”
Section: Correlation Analysismentioning
confidence: 99%